UJI COBA PROFIL AUS UNTUK MENGURANGI KEAUSAN FLENS RODA GERBONG KKBW KA BABARANJANGK - Dahlan Dahlan; Satryo Soemantri (Mesin, 2002)
This research aims at finding out the impact of the change of wheel-tread profile from conical profile of 1:40 to worn profile of ORE S 1002 against the wheel wear rate of the cars. To find out the impact of the change of the wheel-tread profile on the ride quality, ride index is measured at the initial stage of the test. The result shows that the ride index value